Estimation of Near-Surface Loosened Rock Mass Zones in Mountainous Areas by Using Helicopter-Borne and Drone-Borne Electromagnetic Method for Landslide Susceptibility Analysis - Atsuko Nonomura; Shuichi Hasegawa; Akira Jomori; Minoru Okumura; Haruki Ojyuku; Hiroaki Hoshino; Tetsuya Toyama; Atsuyoshi Jomori; Yoshiyuki Kaneda (Remote Sensing, 2025)
Mapping methods for loosened rock mass in mountainous areas are useful for risk management of landslide disasters. Depending on the type of aircraft and sensor, there are several different aerial electromagnetic measurement methods for estimating subsurface structures. Helicopter-borne electromagnetic methods are commonly used. Recently, unmanned aerial vehicles (drones) have been used. By understanding the characteristics of each method, it is possible to choose a suitable method for the target of observation. In this study, resistivity from the frequency-domain helicopter-borne electromagnetic (HEM) method and resistivity from the time-domain drone-grounded electrical-source airborne transient electromagnetic (D-GREATEM) method were compared to estimate loosened zones in mountainous areas. The resistivity cross-sectional profiles were largely similar, but differences were observed near the surface in some zones. The comparative analysis of both methods with outcrop observations revealed that D-GREATEM resistivity data can detect both loosened rock mass from the surface to an approximately 30 m depth located above the groundwater and saturated rock mass. It is because D-GREATEM resistivity was obtained by assuming five layers from the surface to a depth of 40 m. This indicates that D-GREATEM is suitable for estimating near-surface loosened rock mass distribution in the valleys. However, D-GREATEM has a limited observation range. Therefore, it was concluded that the D-GREATEM method is suitable for a detailed and localized estimation of landslide susceptibility near the surface, whereas the HEM method is suitable for wide-area analysis.